Zilina University Concept of Digital Factory - Milan Gregor; Stefan Medvecky (Communications - Scientific letters of the University of Zilina, 2008)
This paper focuses on the Digital Factory technologies, the areas of their application, as well as its benefits for industry. The paper presents the Digital Factory concept built in the framework of co-operation of the University of Zilina and the Central European Institute of Technology (CEIT).